CLOSE ENCOUNTERS: CREATING A SAFE SPACE FOR INTERCULTURAL BIBLE READING1 PART II - Van der Walt, Charlene (Scriptura, 2012)
Theoretically the process of intercultural Bible reading should create a safe space where the voice of the individual can be heard in community with others. It should be a space where the individual is not only free to speak but also to have the innate experience of truly being heard. In this respect the intercultural Bible reading experience becomes a space that promotes human dignity and has the inherent capacity to facilitate social transformation. Although these Bible study groups can ideally be a safe space with the potential for social transformation, the practical reality shows a more complicated dynamic. Two important factors that contribute to the complexity are the ideological framework of individual participants and the underlying power dynamic in the social interaction. To bring the concepts of power and ideology in intercultural Bible reading into focus, an empirical study was conducted. Building on the theoretical discussion in Part I, this contribution will turn to the empirical study. An overview will be provided of the carefully constructed research process which allowed participants time for personal reflection, intimate dialogue as well as group discussion in order to create a free and safe space for creative interaction. In order to critically engage with the data collected, a unique set of qualitative data analysis tools was developed to deal with the issues of power and ideology as mentioned above. The final part of the article will discuss this process of qualitative data analysis and give a brief summary of the research results.